Timing of Surgery and Social Determinants of Health Related to Pathologic Complete Response after Total Neoadjuvant Therapy for Rectal Adenocarcinoma: Retrospective Study of National Cancer Database - Megan Mai; Jodi Goldman; Duke Appiah; Ramzi Abdulrahman; John Kidwell; Zheng Shi (Current Oncology, 2024)
Total neoadjuvant therapy (TNT) for rectal adenocarcinoma (RAC) involves multi-agent chemotherapy and radiation before definitive surgery. Previous studies of the rest period (time between radiation and surgery) and pathologic complete response (pCR) have produced mixed results. The objective of this study was to evaluate the relationship between the rest period and pCR. This study utilized the National Cancer Database (NCDB) to retrospectively analyze 5997 stage-appropriate RAC cases treated with TNT from 2016 to 2020. The overall pCR rate was 18.6%, with most patients undergoing induction chemotherapy followed by long-course chemoradiation (81.5%). Multivariable logistic regression models revealed a significant non-linear relationship between the rest period and pCR (p = 0.033), with optimal odds at 14.7–15.9 weeks post radiation (odds ratio: 1.49, 95% confidence interval: 1.13–1.98) when compared to 4.0 weeks. Medicaid, distance to the treatment facility, and community education were associated with decreased odds of pCR. Findings highlight the importance of a 15–16-week post-radiation surgery window for achieving pCR in RAC treated with TNT and socioeconomic factors influencing pCR rates. Findings also emphasize the need for clinical trials to incorporate detailed analyses of the rest period and social determinant of health to better guide clinical practice.